Self‐reported Resilience of European Farms With and Without the CAP. (21st February 2014) - Peerlings, Jack; Polman, Nico; Dries, Liesbeth
Abstract Firms are able to survive only if they adapt appropriately in response to disturbances. The ability of a farm to continue after a disturbance is defined as resilience. To analyse the resilience of EU farms we explore exit and the number of adaptation strategies that farmers follow under two scenarios. The current CAP will be continued in the base scenario, while it will be abolished in scenario 2. The outcomes show that under both scenarios large, more specialised farms with young farm heads are most resilient, and small more diversified farms headed by old farmers are least resilient.